RELATIONSHIP OF KNOWLEDGE AND ATTITUDE TOWARDS FLOOD DISASTER PREPAREDNESS IN SUKU TIGA VILLAGE NASAL DISTRICT KAUR REGENCY - Devi Listiana; Gita Maya Sari; Vellyza Colin; Muhammad Adithya Abdillah (Poltekkes Kemenkes Bengkulu, 2022)
Flood disasters not only cause casualties but can also cause problems in the health sector. This study aims to study the relationship of knowledge and attitudes towards flood disaster preparedness in Suku Tiga Village of Nasal District, Kaur Regency. This research uses quantitative descriptive methods using analytical observational methods, namely cross-sectional studies. The population in this study is the entire community in Suku Tiga Village of Nasal District Kaur Regency, which amounts to 760 people. The sampling technique used is a simple random sampling technique using the Slovin formula, which amounts to 88 people. This study used primary data obtained from respondents using questionnaires. Data analysis was carried out univariately and bivariately. The results of the study were ob-tained Spearman's rho test results were obtained by 0.298 with p-value = 0.005 < 0.05 significant, meaning that there was a relationship between knowledge and flood disaster preparedness in Suku Tiga Village of Nasal District, Kaur Regency. Because the rho value is located in the interval 0.20 – 0.40 then the category of medium relationship. Spearman's rho test re-sults were obtained by 0.129 with p-value = 0.230> 0.05 was insignificant, meaning that there was no significant relationship between respondents' attitudes and flood preparedness in Suku Tiga Village of Nasal District, Kaur Regency. There is a relationship between knowledge and flood disaster preparedness in Suku Tiga Village of Nasal District, Kaur Regen-cy with the category of medium relationship. There is no relationship be-tween attitude and flood disaster preparedness in Suku Tiga Village of Nasal District, Kaur Regency. It is hoped that nurses will be able to pro-vide training to the community on disaster response so that they can in-crease knowledge and shape community attitudes so that they can improve preparedness in facing flood disasters.